Flexible CO2 Laser Fiber in the Pediatric Airway - Kimberly K. Caperton; G. Paul Digoy (Hindawi Limited, 2011)
Objective. Our institution has been using a novel flexible laser fiber in pediatric surgical airway procedures, which has been quite successful. The purpose of this paper is to present our preliminary experience in the treatment of pediatric airway lesions using this laser technique. Methods. A case series reviewing 40 patients undergoing 95 laser procedures is reported. Indications included removal of suprastomal granulation tissue, removal of granulation after laryngotracheal reconstruction, subglottic and supraglottic stenoses, recurrent respiratory papillomas, subglottic hemangioma, laryngeal cleft, and left main stem bronchus stenosis. Procedures were performed via microdirect laryngoscopy and bronchoscopy. Results. No complications including postoperative glottic webs, concentric scar formation, or airway fires occurred in any of the patients (after the series was completed, we did experience an airway fire. It was a flash flame that was self-limited and caused no long-term tissue injury). Conclusions. The endoscopic application of a new flexible carbon dioxide laser fiber for management of pediatric airways lesions provides good outcomes in selected patients. Distal respiratory papillomas, subglottic stenosis, and granulation tissue are, in our experience, appropriate indications.